Introducing Local Wisdom of Banten Traditional Food through Interactive Cooking Game - Nuhiyah Nuhiyah; Lia Febriyanti; Siti Alwiyah; Wulan Nurjanah; Nashar Nashar (Yupa: Historical Studies Journal, 2025)
Local Wisdom becomes an icon of an area whose existence must be preserved. Banten province has many local wisdoms that must be maintained. One of them is traditional food, which is now being replaced by modern food. The younger generation is now starting to leave the traditional culture, and their ignorance is becoming a problem. The presence of the Interactive Cooking Game, named “Papasakan Interactive Cooking Game,” is expected to be an innovation that increases the knowledge and interest of the younger generation towards traditional Banten food. The research method used is the ADDIE method (analyze, design, development, implementation, evaluation). The respondents of this study included 76 students from the 10th and 11th grades of Senior High School. Various pieces of information about traditional food are obtained through observation and interviews. The results of this research led to the creation of Papasakan: Interactive Cooking Game, an innovative educational game to learn about Banten traditional food. This game contains five traditional foods, including Sate Bandeng from Serang, Rabeg from Cilegon, Mie Laksa from Tangerang, Kue Balok from Pandeglang, and Leumang from Lebak. This game includes the history, uniqueness, and the process of making traditional Banten food. Based on the implementation, the younger generation gave a positive response to the presence of this game. In addition, this game is also considered as an interesting media to introduce knowledge about traditional food to the younger generation.